Defining bioidentical hormones for menopause-related symptoms - Whelan, Anne Marie (Centro de Investigaciones y Publicaciones Farmaceuticas, 2011)
In the last decade, the use of bioidentical hormones (BHs) to treat menopause-related symptoms has become increasingly popular. However, the many different definitions of BHs have led to a great deal of confusion often making it difficult for health care providers to discuss this area with patients. OBJECTIVE: The purpose of this paper was to produce a concise definition of bioidentical hormones, based on a review of the literature. METHODS: Searches, using systematic review methodology, were conducted from inception to June 2010 in PubMed, EMBASE, IPA, The Journal of International Compounding and the Internet to identify definitions of bioidentical hormones. There were no restrictions on type, date or language of publication. Included papers/website included those that contained a definition of BHs. Definitions were extracted, similarities and differences summarized, and these were then examined to produce a concise definition. RESULTS: Sixty-three definitions were found. Based on the analysis of similarities and differences, the following definition, comprised of three components (term being defined; category to which term belongs; distinctive characteristics of term) was produced: “Bioidentical hormones are chemical substances that are identical in molecular structure to human hormones.” CONCLUSIONS: This definition clearly and concisely explains the meaning of BHs which should lead to a common understanding of the term and limit confusion among health care providers, the general public and the scientific community.